A novel ZnO/CQDs/PVDF piezoelectric system for efficiently degradation of antibiotics by using water flow energy in pipeline: Performance and mechanism. (March 2023) - Wang, Zichen; Xiang, Manqi; Huo, Bingjie; Wang, Jingxue; Yang, Lina; Ma, Wei; Qi, Jianguang; Wang, Yinglong; Zhu, Zhaoyou; Meng, Fanqing
Abstract: Using clean and natural energy from the environment to treatment of organic pollutants is a sustainable approach to alleviate energy and environmental problem. This work prepared a novel ZnO/CQDs/PVDF pipe system with excellent piezoelectric properties for efficient tetracycline (TC) degradation. The piezoelectric catalytic activity of ZnO/CQDs/PVDF was excited by hydrodynamic force to achieve a removal rate of 95.17 % of TC within 70 min with a second-order kinetic constant of 0.0185 L∙(mg min) −1, it can still maintain high stability after 35 h cycles. Most importantly, the water flow-driven piezoelectric catalytic system has extremely low energy consumption, is only 17.57 % of that of the ultrasonic system. The CQDs promote the transfer rate of ZnO surfaces charges, and PVDF with flexible β-rich phases were more sensitive to low-frequency pressure responses. ∙OH and ∙O2 - radicals were demonstrated to the main radicals for the degradation of tetracycline. Based on LC-MS results and DFT calculations, the degradation mechanisms of tetracycline molecules, including hydroxylation, C-C, and C-N bond cleavage processes, were successfully predicted. In addition, ZnO/CQDs/PVDF pipe have obvious inhibitory effect on the biotoxicity of intermediates generated during the degradation process and exhibit excellent antibacterial ability. This work demonstrated that ZnO/CQDs/PVDF pipe have efficient utilization of low-frequency water flow energy and shows great potential in practical applications. Graphical Abstract: ga1 Highlights: A novel ZnO/CQDs/PVDF pipe with high piezoelectric activity was developed. The ZnO/CQDs/PVDF pipe can degrade 95.36 % of tetracycline in 70 min at a water flow rate of 0.147 m/s. The energy consumption of the ZnO/CQDs/PVDF pipe system is only 17.57 % of that under the same ultrasonic conditions. The ∙OH and ∙O2 - are the main active species participating in the TC degradation process. Degradation mechanism of tetracycline and the ecotoxicity of the intermediate were introduced in detail.